Mengembangkan Kemampuan Mengenal Konsep Bilangan Melalui Media Kantong Bilangan pada Kelompok A di TK Rinjani DW Unram - Anggun Febriana; I Made Suwasa Astawa; Maharani Maharani; Takasun Takasun (Indonesian Journal of Elementary and Childhood Education, 2023)
This classroom action research aims to develop children's ability to recognize the concept of numbers. The research subjects were 15 children in group A at PAUD Rinjani Unram. The instruments used in this research are recognizing number symbols, connecting objects with numbers and comparing. This study uses the Kemmis and McTaggart model of action research, in two cycles consisting of 2 actions in the first cycle and 2 actions in the second cycle. Collection techniques in this study using interview techniques, observation and documentation. The data obtained were analyzed using qualitative and quantitative descriptive analysis. The results of this study indicate that the development of the ability to recognize the concept of numbers in the first cycle for the Starting to Develop (MB) category was 40% and the Developing According to Expectations (BSH) category increased to 20% and in the second cycle there was an increase of 47% for the Developing According to Expectations (BSH) category. ) and in the Very Well Developed (BSB) category of 33% so that the final data is obtained, namely the average completeness value of 80%. Based on the description above, it can be concluded that through the media of number pockets in group A children are able to improve the ability to recognize the concept of numbers.